Supervisory performance in telework: the role of job demands, resources, and satisfaction with telework - Peiró, José M.; Bravo-Duarte, Felipe; González-Anta, Baltasar; Todolí-Signes, Adrián (Frontiers in Organizational Psychology, 2024)
Digitalization and the pandemic have transformed work, increasing flexibility and remote arrangements. A critical factor in these transformations' success is supervisors' competencies. Consequently, new tools for assessing supervisory performance are required, particularly considering subordinates' evaluations. This study investigates the role of three telework resources (structural support, telework readiness, and monitorization) and three demands (workload, isolation, and information overload) in predicting employees’ evaluation of supervisors, with satisfaction with telework as a moderator. A survey among 322 Spanish teleworkers revealed that organizational structural support positively correlates with subordinates’ evaluation of their supervisor, while monitorization shows a negative relationship. Telework demands studied demonstrated no significant relationship with the outcome. Interaction effects between resources and satisfaction with telework added predictive power. Implications for workers and organizations are discussed.